Implementation of the Democratic Leadership Style of the Ganra Village Head in Soppeng Regency - Suprianto, Suprianto; Fitriani, Fitriani; Nasrullah, Muh. (Jurnal Office, 2023)
Leadership style is very important in an organization or agency. Because the leadership style possessed by each leader is able to influence employee performance and the effectiveness of achieving organizational goals. This research aims to find out how the democratic leadership style of the Ganra village head in Soppeng Regency is implemented. To achieve this goal, researchers used a qualitative approach with descriptive research type. In this research, data analysis techniques are used which consist of data reduction, data presentation and drawing conclusions. The results of the research show that the implementation of the democratic leadership style of the Ganra village head is implemented well, seen from the leader's success in implementing democratic leadership by means of deliberation in making decisions. Appreciating the potential of subordinates, looks at how the village head is able to organize subordinates according to their respective abilities, gives appreciation to the performance carried out by employees and provides opportunities for employees to take part in various training to increase employee competency. Collaborating with his subordinates, we can see how the village head is able to establish good relationships by being actively involved in implementing the work program. This research can be used as a reference and knowledge about the application of a democratic leadership style using qualitative research methods.